Convergence rates on periodic homogenization of p-Laplace type equations. (October 2019) - Wang, Li; Xu, Qiang; Zhao, Peihao
Abstract: In this paper, we find some error estimates for periodic homogenization ofp-Laplace type equations under the same structure assumption on homogenized equations. The main idea is that by adjusting the size of the difference quotient of the correctors to make the convergence rate visible. In order to reach our goal, the corresponding flux corrector with some properties are developed. Meanwhile, the shift-argument is in fact applied down to ε scale, which leads to a new weighted type inequality for smoothing operator with the weight satisfying Harnack's inequality in small scales. As a result, it is possible to derive some large-scale estimates. We finally mention that our approach brought in a systematic error (this phenomenon will disappear in linear and non-degenerated cases), which was fortunately a quantity o ( ε ) here.